Professional Identity in Nursing: A Concept Analysis Across Professions: Concept Review Article - Brittany Haskell (Research and Theory for Nursing Practice, 2026)
Background: The concept of professional identity is gaining traction within the nursing profession through intentional steps to define the concept and include it as an educational benchmark for all nurse graduates. Defining attributes of professional identity differ across professions, which necessitates comparison for a robust understanding. Purpose: The aim of this conceptual analysis is to identify defining attributes of one’s professional identity in nursing by comparing conceptual usage of professional identity throughout history and current defining attributes within the professions of medicine, engineering, and teaching using the Walker and Avant method. Articles appraising the history of the concept of professional identity, conceptual definitions, or defining attributes within the profession were synthesized for comparison. Results: The nursing profession was late to recognize and conceptualize professional identity for individual nurses when compared with medicine, engineering, and teaching. Conceptualization of professional identity has surged in the last decade. Defining attributes of one’s professional identity include perception and feeling as a member of a profession; individual values, beliefs, and actions that align with the larger profession; understanding of a distinct practice; foundational research-based knowledge through formal and ongoing education; and reflection on relationships and experiences that impact values and beliefs throughout a career. Implications for the Profession: A more robust conceptualization of professional identity has the capability of enhancing nursing theory, research, and practice to establish nurses with a strong sense of belonging within the profession.